2020
DOI: 10.1088/1748-9326/abb852
|View full text |Cite
|
Sign up to set email alerts
|

Common but differentiated leadership: strategies and challenges for carbon neutrality by 2050 across industrialized economies

Abstract: Given their historic emissions and economic capability, we analyze a leadership role for representative industrialized regions (EU, US, Japan, and Australia) in the global climate mitigation effort. Using the global integrated assessment model REMIND, we systematically compare region-specific mitigation strategies and challenges of reaching domestic net-zero carbon emissions in 2050. Embarking from different emission profiles and trends, we find that all of the regions have technological options and mitigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 46 publications
0
42
1
1
Order By: Relevance
“…In a similar vein, Kato and Kurosawa ( 2019 ) examined 2050 emissions reduction of 80% and more, and found that reduced service demands and the availability of BECCS would be vital to achieve 90% emissions reduction. Schreyer et al ( 2020 ) used the ReMIND model to compare 2050 net-zero targets for Australia, the European Union, Japan, and the United States, and found a smaller share of variable renewables in Japan because of its high population density.…”
Section: Policy and Literature Reviewmentioning
confidence: 99%
“…In a similar vein, Kato and Kurosawa ( 2019 ) examined 2050 emissions reduction of 80% and more, and found that reduced service demands and the availability of BECCS would be vital to achieve 90% emissions reduction. Schreyer et al ( 2020 ) used the ReMIND model to compare 2050 net-zero targets for Australia, the European Union, Japan, and the United States, and found a smaller share of variable renewables in Japan because of its high population density.…”
Section: Policy and Literature Reviewmentioning
confidence: 99%
“…29 A leading determinant in the extent of fossil fuel reductions in net-zero scenarios appears to ll be CDR costs, availability, and deployment with higher fossil fuel use in scenarios with higher CDR deployment, a point made in intra-model comparisons with different CDR assumptions. 19,21,25 Note the qualitative agreement in high-level findings between country-level netzero studies and global-scale analysis for metrics presented in Figure 1, though magnitudes differ as do more specific features of scenarios (e.g., renewables shares, infrastructure buildout). This consistency could suggest that using top-down scenarios to diagnose trends is a promising approach, though analysis with appropriate resolution should be consulted depending on questions decision-makers are trying to answer.…”
Section: Electrification Of End Uses and Alternative Fuels In Reaching Net Zeromentioning
confidence: 64%
“…1 Although Europe does not have a carbon dioxide removal (CDR) strategy yet, [1][2][3][4] CDR via bio-energy with carbon capture and storage (BECCS) will most likely be needed to counteract residual emissions from hard-to-abate sectors. [5][6][7][8][9][10][11][12] To reach carbon-neutrality, it has been estimated that up to 7.5 billion tons of CO 2 may have to be sequestered through BECCS in Europe until 2050. 13 BECCS involves the capture and permanent sequestration of biogenic CO 2 produced during energy conversion from biomass [14][15][16][17] and is considered promising due to its degree of commercial maturity.…”
Section: Introductionmentioning
confidence: 99%